2023
DOI: 10.1111/acfi.13046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the interactive and diagnostic uses of performance measurement systems on procedural fairness perception, cooperation and performance in supply alliances

Abstract: We examine the effects of interactive and diagnostic uses of performance measurement systems (PMSs) on two behavioural factors (procedural fairness perception and cooperation) in inter‐firm alliances. We further investigate whether the two behavioural factors mediate the relationship between PMS uses and alliance performance. We find that both interactive and diagnostic uses of PMS are significantly related to procedural fairness perception but only the interactive use is significantly related to cooperation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 214 publications
(472 reference statements)
0
1
0
Order By: Relevance
“…According to (Su et al, 2022), the results showed that justice positively influences performance. According to (Mahama & Wang, 2023), It has been asserted that the concept of fairness significantly influences manager performance. The idea of fairness in performance evaluation has the potential to be a motivating factor for managers, encouraging them to achieve better results.…”
Section: Introductionmentioning
confidence: 99%
“…According to (Su et al, 2022), the results showed that justice positively influences performance. According to (Mahama & Wang, 2023), It has been asserted that the concept of fairness significantly influences manager performance. The idea of fairness in performance evaluation has the potential to be a motivating factor for managers, encouraging them to achieve better results.…”
Section: Introductionmentioning
confidence: 99%